Contemporary Human Rights Safeguards in Islamic Law Justice: A Comparative Study in Indonesia, Saudi Arabia, and Egypt - Sahat Maruli Tua Situmeang; Athari Farhani; Subagyo Sri Utomo; Musa Darwin Pane (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
This study examines the protection of human rights in the context of arrest, detention, and judicial remedies from the perspectives of Islamic law and contemporary legal systems through a comparative analysis of Indonesia, Saudi Arabia, and Egypt. Employing a normative legal research method, the study draws upon authoritative legal sources, including international human rights instruments such as the Universal Declaration of Human Rights (1948) and the International Covenant on Civil and Political Rights, as well as relevant national legislation in the three jurisdictions. The findings reveal distinct models in the integration of Islamic legal principles within state legal frameworks. Indonesia represents a constitutional democratic model with a relatively high degree of justiciability, reflected in robust judicial review mechanisms and stronger guarantees of due process. In contrast, Saudi Arabia embodies a centralized monarchical system, where judicial independence and oversight of administrative detention remain comparatively limited. Egypt, meanwhile, exhibits a hybrid model that combines civil law traditions with Islamic legal influences, resulting in a moderate level of judicial independence. Importantly, the study demonstrates that the alignment between core Islamic legal principles—such as justice (‘adl), the presumption of innocence, the prohibition of arbitrary detention, and access to legal remedies—and contemporary human rights standards is not merely normative; rather, it is operationalized through three key mechanisms: the contextual reinterpretation of fiqh, the codification of norms into national legislation, and the strengthening of judicial practices through rulings that uphold due process of law. This research contributes to the scholarly discourse by offering a comparative framework that bridges Islamic jurisprudence and modern human rights law, while also proposing practical pathways for legal harmonization. It recommends the systematic integration of Islamic legal values into contemporary human rights protection through adaptive reinterpretation, legislative reform, and the strengthening of judicial independence and institutional capacity.